2020
DOI: 10.1007/s10067-020-05133-0
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Cidofovir as an adjunctive therapy in a patient of adenovirus-induced macrophage activation syndrome in systemic arthritis

Abstract: A 5-year-old female child, with known systemic juvenile idiopathic arthritis diagnosed at 18 months of age (on low dose Prednisolone + Methotrexate + Leflunomide + Tocilizumab), presented with fever for 1 day, vomiting, drowsiness followed by seizures. On admission to PICU, she was drowsy, tachycardic, tachypneic, with rashes, and hepatosplenomegaly. Lab findings showed thrombocytopenia, leucopenia, low ESR, normal CRP, elevated liver enzymes, high ferritin, LDH, and triglycerides suggestive of macrophage acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Human adenovirus infection is seldom associated with HLH. The majority of reported cases pertain to children, while only a few cases have involved adults [58,[86][87][88]. A recent study investigated the risk factors associated with HLH development in children with severe adenovirus pneumonia and found that patients with longer duration of fever (over 12.5 days) and elevated triglyceride levels (over 3.02 mmol/L) were at higher risk of developing HLH [89].…”
Section: Human Adenovirus and Parvovirus B19mentioning
confidence: 99%
“…Human adenovirus infection is seldom associated with HLH. The majority of reported cases pertain to children, while only a few cases have involved adults [58,[86][87][88]. A recent study investigated the risk factors associated with HLH development in children with severe adenovirus pneumonia and found that patients with longer duration of fever (over 12.5 days) and elevated triglyceride levels (over 3.02 mmol/L) were at higher risk of developing HLH [89].…”
Section: Human Adenovirus and Parvovirus B19mentioning
confidence: 99%
“…MAS identifies hemophagocytic syndrome in children with systemic juvenile idiopathic arthritis (sJIA) and other chronic rheumatic diseases [ 1 ]. MAS may develop spontaneously, as a complication of active disease, or can be induced by an infection, changes in drug therapy, or a toxic effect of medication [ 2 ]. Most cases (58% to 88.9%) have possible triggering factors prior to the onset of MAS [ 1 ].…”
Section: Introductionmentioning
confidence: 99%